Microstructural Morphology Of Rheocast A319 Aluminium Alloy - Ahmad Muhammad, Aziz; Mohd Zaidi, Omar; Zainuddin, Sajuri; Mohd Shukor, Salleh (SAGE Publications Ltd., 2016)
This article examines the evolution of the microstructure of A319 aluminium alloy as it flows along a cooling slope plate and discusses the type and influence of the intermetallic compounds thus formed. Numerous past research studies have analysed the microstructural transformation of alloys in a mould, but few researchers have investigated this phenomenon on the cooling slope plate. A change in the microstructure of the alloy from dendritic to non-dendritic is clearly obtained as the alloy moves from the impact zone to bottom zone on the cooling slope plate. It is important to clarify the mechanism of microstructural evolution through nucleation and fragmentation of the primary phase arm for fundamental understanding of research. Analysis by optical microscope and scanning electron microscope reveals the evolution of the microstructure and intermetallic compounds of A319 as it progresses along the cooling slope plate. The Vickers test was used to determine the hardness of the alloy thus produced. The results show the influence of the mould in obtaining a spheroidal microstructure; the microstructure in the bottom zone of the cooling slope plate is nearly spheroidal rather than fully spheroidal. The hardness of the alloy is enhanced when the microstructure is spheroidal and when the Mg2Si compound is present in the alloy.